Creation of new medical polyurethane foams with cycloserine - Karpenko, O.S.; Rozhnova, R.A.; Galatenko, N.A.; Kiselova, T.O. (Reports of the National Academy of Sciences of Ukraine, 2017)
New polyurethane foams which contain cycloserine and can be used as polymeric materials for medical goals are created. The polymeric materials obtained are investigated by physical and mechanical methods and IRspectroscopy. The physical immobilization of cycloserine on a polymeric carrier is proved. It is established that if cycloserine is introduced into the polymer matrix, the rupture strength is increased.